Distortion Analysis due to Heat Treatmen Process on Two Layers Component - NYOMAN PRIMA YANA (NIM 13704009), I
Heat treatment process is done for altering materials properties by heating it and controlling the cooling rate. The existence of phase transformation in heat treatment process makes volume changing at the materials. If we do not control internal stress due to volume changing, it will create unexpected flaw, for instance, distortion and crack. Therefore, it's a necessary to know the cause of the flaw, especially distortion, and it will be explained in this research. Two kinds plain carbon materials containing different carbon presentage each, are used in this research. Both of specimens were formed in two layers, which will make thickness difference. Research was done by heating the materials until reaching austenite temperature, holding it, and then cooling it rapidly (quenching) in water medium. Material A was heated until 810 oC and material B until 830 oC. Each material was held at that temperature for 2 hours. Distortion phenomena could be seen by measuring the changing of dimension from the beginning and the last. By this research, we will know that if a material is heated until reaches austenite temperature and then quenched, it will create residual stress. Therefore, more a material contains high carbon, and has different thickness, more possibility of distortion phenomena will be happened. The cooling rate and value of layer thickness difference will be very influencing in distortion phenomena.